MODEL OF EMPOWERMENT OF TANIMBAR WHIEAVING CRAFTSMAN IN THE CITY OF AMBON - Bakarbessy, Derek; Laurens, Samson (JURNAL BADATI, 2023)
This research aims to ; (1) to find out the profiles of Tanimbar Weaving Craftsmen and (2) to find out the strategy for developing the Tanimbar Weaving Craftsmen in Ambon City. This research is a case study research with descriptive research type. Descriptive research is intended for exploration and clarification of social phenomena or realities, by describing a number of variables relating to the problem under study. The results showed that; (1) the Tanimbar Weaving Craftsmen has a large enough potential to be developed as one of the potential empowerment of craftsmen in Ambon City, (2) the strategy for empowering craftsmen through developing the potential for the Tanimbar Weaving Craftsmen can be carried out through the empowerment process which includes; (a) awareness, (b) organizing, (c). resource delivery.